1992
DOI: 10.1080/00140139208967813
|View full text |Cite
|
Sign up to set email alerts
|

External finger forces in submaximal five-finger static pinch prehension

Abstract: Small conductive polymer force sensors were attached to the distal phalangeal pads for measuring individual finger forces exerted during submaximal static pinch. A linear force summing strain gauge dynamometer for measuring resultant five-finger pinch force was grasped vertically using a neutral wrist posture. Individual finger forces were measured at fixed total pinch force levels of 10%, 20%, and 30% of maximum voluntary exertion using pinch spans of 45 mm and 65 mm. Total pinch force and individual finger f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 13 publications
4
42
0
Order By: Relevance
“…Many examples of this exist in the literature (e.g., Kinoshita et al 1995;Latash et al 1998a,b;Li et al 1998;Radwin et al 1992). Tangential force-sharing stability when load is changed is also not new .…”
Section: Reproducibility Of Force-sharing Patternsmentioning
confidence: 99%
“…Many examples of this exist in the literature (e.g., Kinoshita et al 1995;Latash et al 1998a,b;Li et al 1998;Radwin et al 1992). Tangential force-sharing stability when load is changed is also not new .…”
Section: Reproducibility Of Force-sharing Patternsmentioning
confidence: 99%
“…It is apparent from the simulation that the maximum applied force (i.e. 5[N], mean maximum external finger force [6]) on the cantilever is significantly lower than the yield strength of the material selected for manufacturing the real finger ( i.e. ABS plastic) [7].…”
Section: Designmentioning
confidence: 99%
“…However, the study of Radwin et al (1992) observed only three levels of grip forces at slightly low levels of less than 30% MVC, and therefore there is a difficulty to compare with contributions upon exerting bigger forces.…”
Section: Introductionmentioning
confidence: 99%
“…A study on each finger's contribution is important to establish hand's biomechanical models, and design and improve hand tools and manual activities (Radwin et al, 1992). Especially, the acquisition of each finger's contribution and biomechanical data in the ergonomics field is not only essential information in the design of hand tools or prosthetic hand (Crago et al, 1991), robotic arm (Mason and Salisbury, 1985), and working environment, but can be used as vital information in the judgment of hand function's abnormality .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation